HUBUNGAN MANAJEMEN KEUANGAN YANG EFEKTIF DENGAN KUALITAS LAYANAN PENDIDIKAN DI PERGURUAN TINGGI - Riinawati (Berajah Journal, 2025)
Effective financial management plays a crucial role in improving the quality of educational services in higher education institutions. Proper financial management allows institutions to allocate resources optimally across various aspects, such as providing learning facilities, enhancing faculty competencies, developing curricula, and offering scholarships to students. Financial transparency and accountability are also key factors in maintaining stakeholder trust and ensuring institutional sustainability. This study employs a literature review method to analyze the relationship between financial management effectiveness and the quality of educational services in higher education institutions. The findings indicate that institutions implementing efficient, transparent, and accountable financial systems tend to have higher competitiveness and provide better educational services to students.